2018
DOI: 10.1073/pnas.1813927115
|View full text |Cite
|
Sign up to set email alerts
|

Basophils trigger emphysema development in a murine model of COPD through IL-4–mediated generation of MMP-12–producing macrophages

Abstract: Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality worldwide. It has generally been considered a non-Th2-type lung disorder, characterized by progressive airflow limitation with inflammation and emphysema, but its cellular and molecular mechanism remains ill defined, compared with that of asthma characterized by reversible airway obstruction. Here we show a previously unappreciated role for basophils at the initiation phase of emphysema formation in an elastaseinduced mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 49 publications
4
95
1
2
Order By: Relevance
“…For example, basophils may amplify a localised type 2 response by IL-4 secretions [11,43], are activated by IL-33 and thymic stromal lymphopoietin, and may release a variety of proinflammatory cytokines in addition to histamine. In recent experimental models, basophils have been identified as having a role in emphysema development [44] and they have also been linked to the defence against COPD-relevant bacteria and viruses [41]. Basophils may thus, beside their harmful pathogenic capacity, also play a protective role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, basophils may amplify a localised type 2 response by IL-4 secretions [11,43], are activated by IL-33 and thymic stromal lymphopoietin, and may release a variety of proinflammatory cytokines in addition to histamine. In recent experimental models, basophils have been identified as having a role in emphysema development [44] and they have also been linked to the defence against COPD-relevant bacteria and viruses [41]. Basophils may thus, beside their harmful pathogenic capacity, also play a protective role.…”
Section: Discussionmentioning
confidence: 99%
“…Model of viral exacerbation with and without prior smoke exposure Archive lung mouse tissues [21,22] were used to investigate potential eosinophil chemotaxis responses and formation of patchy eosinophilia in wild-type or IL-33-deficient mice terminated 6 days after exposure to virus (mouse-adapted H1N1 influenza A; A/FM/1/47-MA) with or without 11 days of prior daily 44.5 (43.2-45.9)% predicted); ¶ : the mean age of the study group was 64 years; + : data missing from one patient; § : one patient with unknown medical history; ƒ : p<0.01 versus smokers without COPD; ## : p<0.05 versus patients with GOLD stage II-III COPD; ¶ ¶ : p<0.005 versus never-smokers; ++ : p<0.0001 versus never-smokers; § § : p<0.0001 versus smokers without COPD; ƒƒ : p<0.0005 versus patients with GOLD stage I COPD; ### : p<0.005 versus patients with GOLD stage II-III COPD; ¶ ¶ ¶ : p<0.01 versus never-smokers; +++ : p<0.05 versus smokers without COPD; § § § : p<0.02 versus patients with GOLD stage I COPD.…”
Section: Quantitative Ihc and Computerised Image Analysismentioning
confidence: 99%
“…After BAL, lungs were dissected into pieces for enzyme digestion in RPMI-1640 medium containing DNase I (0.15 mg/mL, Sigma, USA) and collagenase II (1 mg/mL, Sigma, USA) at 37 ℃ for 1 h [27,28]. The digested tissues were homogenized by vigorous shaking and passed through a 70-μm cell strainer (BD, USA).…”
Section: Preparation Of Lung Single Cell Suspensionsmentioning
confidence: 99%
“…Basophils currently play an obscure role in COPD, however a recent study showed that basophil-derived IL-4 plays a crucial role in the initiation of emphysema in a murine COPD model, driving the production of MMP-12 by interstitial macrophages [146]. This highlights that basophils may play a bigger role in COPD and this is worth further investigation.…”
Section: Granulocyte-targeted Therapies For Copdmentioning
confidence: 99%